FEASIBILITY STUDY OF XIV HIU PUTIH HOUSING, PALANGKA RAYA CITY BASED ON PERMENPERA No 22/PERMEN/M/2008 - Ardiansyah; Samuel Layang (Jurusan Pendidikan Teknologi Dan Kejuruan, 2021)
This study aims to assess the feasibility of housing type 36 which was built by PT. Toraa Graha Utama at the Perumahan Hiu Putih XIV Palangka Raya City, Central Kalimantan based on Permenpera Nomor 22/Permen/M/2008. The study refers to livable houses that apply a healthy and safe environment supported by public infrastructure, facilities and utilities regulated by technical guidelines for minimum service standards in the district/city housing sector. This study uses a descriptive qualitative method and uses analysis. The research instruments were in the form of questionnaires and interviews with informants. There are 30 house samples. Based on the results of the study, it is known that the Perumahan Hiu Putih XIV has implemented the provisions for livable houses, and meets the building safety requirements, minimum adequacy of building area and the health of its occupants, and has also implemented environmental criteria equipped with environmental infrastructure, and public facilities. The results of calculations from respondents' answers conducted at the time of the interview obtained 88% of the total achievement of livable houses and a healthy and safe environment supported by infrastructure, facilities and public utilities.